Multifunctional MXene for Thermal Management in Perovskite Solar Cells - Zhongquan Wan; Runmin Wei; Yuanxi Wang; Huaibiao Zeng; Haomiao Yin; Muhammad Azam; Junsheng Luo; Chunyang Jia (Nano-Micro Letters)
Highlights Incorporating Ti3C2TX nanosheets enhanced perovskite thermal conductivity (from 0.236 to 0.413 W m−1 K−1) and reduced operating temperature by ~3 °C under illumination, mitigating heat-induced degradation. Ti3C2TX offers multiple additional functionalities, including defect passivation, improved charge transfer efficiency, and optimized energy level alignment. Champion power conversion efficiency (PCE) reached 25.13% (vs. 23.70% control). Retained 80% PCE after 500 h at 85 °C/RH = 30 ± 5%, outperforming control (58% after 200 h). MPP tracking showed 70% PCE retention after 500 h in N2 (vs. 20% control).